Service-oriented computing -- ICSOC 2015 Workshops : WESOA, RMSOC, ISC, DISCO, WESE, BSCI, FOR-MOVES, Goa, India, November 16-19, 2015, Revised selected papers /: WESOA, RMSOC, ISC, DISCO, WESE, BSCI, FOR-MOVES, Goa, India, November 16-19, 2015, Revised selected papers. (2016) - Unknown
No abstract available